A framework for computer‐aided design and manufacturing of habitat structures for cavity‐dependent animals. Issue 4 (13th February 2022) - Parker, Dan; Roudavski, Stanislav; Jones, Therésa M.; Bradsworth, Nick; Isaac, Bronwyn; Lockett, Martin T.; Soanes, Kylie
Abstract: The decline of critical habitat structures, such as large old trees, is a global environmental challenge. The cavities that occur in these trees provide shelter and nesting sites for many species but can take centuries to develop. Artificial cavities, including nest boxes and carved logs, offer an increasingly important conservation response. However, current methods of designing, manufacturing and deploying such habitats have constraints that limit innovation, feasibility and effectiveness. In response, this article aims to provide new and broadly useable methods that can improve the design of habitat structures for cavity‐dependent animals. To address the shortcomings of existing methods, we develop an approach that uses computer‐aided design techniques of generative and parametric modelling to produce structures that satisfy stakeholder needs, computer‐aided manufacturing techniques of 3D printing and augmented‐reality assembly to build functional prototypes, and computer‐assisted techniques of laser scanning and data‐driven design to support installation, monitoring and iterative improvement of designs. We demonstrate this approach through a case‐study project that designs and instals habitat structures for the powerful owl Ninox strenua, a cavity‐dependent and threatened bird. Through a comparison with existing methods, our pilot study shows that computer‐aided design and manufacturing can provide novel and useful approaches to develop artificial habitat‐structures. Computer‐aided design finds geometries that approximate the complex characteristics of natural tree cavities and automatically produces new versions to suit diverse sites or species. Computer‐aided manufacturing integrates materials that match the performance of naturally occurring habitat structures and facilitates the assembly of complex geometries by non‐experts. Computer‐assisted techniques produce precisely fitting and easy‐to‐instal designs, which support gradual improvement through ongoing prototyping and evaluation. These capabilities highlight how advanced design techniques can improve aspects of artificial habitat‐structures through geometric innovation, novel construction techniques and iterative exploration. Significantly, computational approaches can result in designs that can perform well, are easy to construct and instal and are applicable in many situations. Our reusable workflow can aid in the tasks of practical conservation and support ecological research by effectively negotiating the needs of both humans and target species.